The colours of love: facial thermal reactions of people thinking about their lovers. Issue 2 (3rd April 2022) - Cannas Aghedu, Fabio; Cardone, Daniela; Merla, Arcangelo; Troïan, Jaïs; Bisiacchi, Patrizia S.; Lux-Sterritt, Laurence; Graziani, Pierluigi
ABSTRACT: Romantic love involves peculiar psychological and neural processes that are closely connected with autonomic-visceral changes. The present study aimed at investigating the thermal response associated to the love induction task. The facial thermal imprints of forty-four people who were in love and in romantic relationships at the time of the experiment were recorded. Thermal signals were extracted from six regions of interest (ROIs), positioned on the tip of the nose, the upper nose and the perioral areas. The experimental protocol was composed of two conditions, randomised among the subjects: love and control conditions. In the first one, participants were initially asked to think about their partners, then to keep continuing this task while listening to a song related to their relationships; in the second one, they were asked to think about someone else's relationship, then keep continuing this task while listening to positive-content song, unknown to the specific participant. The results showed that, when experiencing the love condition, the temperature of the nasal tip of the subjects increased, compared to the control condition. Moreover, the data showed that music induced a far more intense peripheral response. Thinking about their partners whilst listening to the love song caused higher peripheral (nose temperature) and subjective responses than with the unknown happy song, which suggests that love induction task activates peculiar patterns that go beyond mere positive feelings.